Custom-made sulfonated poly (vinylidene fluoride-co-hexafluoropropylene) nanocomposite membranes for vanadium redox flow battery applications. (October 2020) - Divya, Kumar; Rana, Dipak; Sri Abirami Saraswathi, Meenakshi Sundaram; Nagendran, Alagumalai
Abstract: Sulfonated poly (vinylidene fluoride-co-hexafluoropropylene) (SPVDF-co-HFP) based nanocomposite proton exchange membranes (PEM) are fabricated by simple solution casting method using polydopamine coated exfoliated molybdenum disulfide (PDA-MoS2 ) nanosheets as an alternative for Nafion® in vanadium redox flow batteries (VRFBs). PDA-MoS2 is synthesized by the etching of exfoliated MoS2 nanosheets with dopamine molecule by self-polymerization method. Various characteristic results clearly demonstrated that the incorporated PDA-MoS2 nanosheets homogeneously distributed into the SPVDF-co-HFP matrix and the presence of NH/NH2 group electrostatically interacts with SPVDF-co-HFP to form a strong acid-base pair and thus enhances the proton transport via Grotthuss type mechanism. Besides, the improvement in surface hydrophilicity provides the vehicle type conduction also. As a result, SPVDF-co-HFP/PM nanocomposite membranes showed higher proton conductivity in comparison with the pristine membrane. Especially SPVDF-co-HFP/PM-1 membrane demonstrated the excellent proton conductivity of 5.24 × 10 −3 Scm −1 at 25 °C, lower vanadium-ion permeability of 1.05 × 10 −8 cm 2 min −1 and highest membrane selectivity of 49.9 × 10 4 Scm −3 min. On the other hand, vanadium-ion stability of the membrane increased by adding the PD-MoS2 content is attributed to their strong electrostatic attraction towards the polymer matrix. Overall results suggested that the SPVDF-co-HFP/PM-1 nanocomposite membrane is found to be a better alternative for commercially costly Nafion in VRFB applications. Graphical abstract: Image 1 Highlights: Bio-inspired polydopamine coated exfoliated molybenum disulfide (PDA-MoS2 ) nanosheets are successfully synthesized. PDA-MoS2 nanosheets effectively block the vanadium-ion permeation via SPVDF-co-HFP membranes up to 1.05 × 10 −8 cm 2 min −1 . Acid-base pair formation between SPVDF-co-HFP with PDA-MoS2 offers a new proton conduction pathway. SPVDF-co-HFP/PDA-MoS2 membranes showed higher chemical stability and found appropriate for use in VRFBs. SPVDF-co-HFP/PDA-MoS2 membranes are superior to bare SPVDF-co-HFP and Nafion membranes.